Metabolic Stress and Blood Flow Restriction Training as Interventions for Skeletal Muscle Atrophy following Musculoskeletal Injury - Michael Bower (International Universities Strength and Conditioning Association, 2021)
Skeletal muscle loss poses significant health issues to both the general clinical population, but also athletes recovering from musculoskeletal (MSK) injury. Whilst resistance training is known to induce skeletal muscle hypertrophy (SMH), 70% of an individual's one repetition maximum (1RM) is required to elicit such changes. This is not always feasible for the abovementioned populations due to rheumatic limitations and thus, targeting metabolic stress as a stimulus for skeletal muscle hypertrophy may be more favourable than that of mechanical tension. Blood Flow Restriction (BFR) training occludes venous out-flow, whilst sustaining arterial in-flow to the working muscle resulting in a pooling of anaerobic metabolites. As a result, resistance training loads as low as 20% 1RM are capable of eliciting hypertrophic effects equivalent to training at heavier loads, and this is mediated through both endocrine and intramuscular mechanisms. Safe administration of BFR is paramount, especially when prescribing to post-surgical athletes. As such, the coach or clinician in question must take careful consideration regarding pressure application, rest periods and various patient characteristics such as post-surgical timeframe and overall health status.